Illustrations of Old Testament History - Barnett, R. D. (1966)
esp. 1. The Babylonian Legend of the Flood; 2. The ‘Amarna Letters’ and the Cities of Canaan; 11. Shalmaneser III; 12. The Homage of Jehu; 13. Tiglath-Pileser III Invades Palestine; 14. The Capture of Samaria; 15. Sennacherib and Hezekiah; 16. The Siege of Lachish; 19. The End of Assyria, the Fall of Nineveh, and the Capture of Jerusalem.